2002
DOI: 10.1038/nn910
|View full text |Cite
|
Sign up to set email alerts
|

Spatial memory dissociations in mice lacking GluR1

Abstract: Gene-targeted mice lacking the AMPA receptor subunit GluR1 (GluR-A) have deficits in hippocampal CA3-CA1 long-term potentiation. We now report that they showed normal spatial reference learning and memory, both on the hidden platform watermaze task and on an appetitively motivated Y-maze task. In contrast, they showed a specific spatial working memory impairment during tests of non-matching to place on both the Y-maze and an elevated T-maze. In addition, successful watermaze and Y-maze reference memory perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

34
336
7

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 313 publications
(377 citation statements)
references
References 25 publications
34
336
7
Order By: Relevance
“…The aim of the present study was to simultaneously assess spatial WM and RM in GluRA Ϫ/Ϫ mice, using a radial-arm maze task in which the same three of six arms are always baited, but in which the food rewards are not replaced within a trial. Whereas previously we demonstrated a clear dissociation between spatial WM and RM using different behavioral tests conducted separately at different times and in different spatial environments with different spatial cues (Reisel et al, 2002), the present experiments allow WM and RM components of spatial learning to be dissociated not only within subjects but also within the same trial. Importantly, the WM and RM components of the task are assessed using identical spatial cues.…”
Section: Introductioncontrasting
confidence: 63%
See 1 more Smart Citation
“…The aim of the present study was to simultaneously assess spatial WM and RM in GluRA Ϫ/Ϫ mice, using a radial-arm maze task in which the same three of six arms are always baited, but in which the food rewards are not replaced within a trial. Whereas previously we demonstrated a clear dissociation between spatial WM and RM using different behavioral tests conducted separately at different times and in different spatial environments with different spatial cues (Reisel et al, 2002), the present experiments allow WM and RM components of spatial learning to be dissociated not only within subjects but also within the same trial. Importantly, the WM and RM components of the task are assessed using identical spatial cues.…”
Section: Introductioncontrasting
confidence: 63%
“…For example, Zamanillo et al (1999) showed that gene-targeted mice lacking the AMPA receptor subunit glutamate receptor-A (GluRA) (GluR1) demonstrated normal acquisition of a spatial reference memory (RM) water maze task, despite an absence of hippocampal LTP at CA33 CA1 synapses. More recently, Reisel et al (2002) have shown that, although water maze acquisition is normal in these GluRA Ϫ/Ϫ mice, they are dramatically impaired during discretetrial, rewarded alternation on the elevated T-maze, another hippocampus-dependent memory task. This has led us to suggest that GluRA-dependent forms of synaptic plasticity may be required for spatial working memory (WM) (e.g., T-maze), but that GluRA-independent mechanisms in the hippocampus may be sufficient to support spatial RM (e.g., water maze).…”
Section: Introductionmentioning
confidence: 99%
“…As such, these data build upon an elegant series of studies demonstrating selective performance deficits on tests for working memory and cognitive flexibility, behaviors that are also impaired in schizophrenia. [30][31][32][33] Pharmacological blockade of NMDA receptor function with non-selective NMDA antagonist such as phencyclidine and ketamine can induce temporary psychosis in normal human subjects and provoke symptoms in schizophrenics. 51 GluR1 KO have been found to exhibit a loss of NMDA receptor-mediated long-term potentiation, but normal NMDA-receptorinduced Ca 2 þ influx and NR1 expression, in CA1 hippocampal neurons.…”
Section: Discussionmentioning
confidence: 99%
“…[24][25][26][27][28][29] Previous studies have demonstrated that GluR1 knockout mice (KO) 30 exhibit behavioral abnormalities on tests for cognition, motor function and responses to drugs of abuse. [30][31][32][33][34][35][36][37] In the present study, we sought to extend these data by assessing these mice for a variety of 'schizophrenia-related' phenotypes. In addition, given the wealth of evidence implicating dysfunction of dopamine (DA) neurotransmission in schizophrenia 2 and the major interaction between the dopamine and glutamate systems, 2,38 we evaluated regulation of extracellular striatal DA in GluR1 KO in vivo using high-speed chronoamperometry.…”
Section: Introductionmentioning
confidence: 99%
“…The fast glutamatergic neurotransmission in the mammalian brain is mediated mainly via AMPA (a-amino-3 hydro-5 methyl-isoxazole propionic acid) receptors, and their regulated activity is critical for normal synaptic transmission and specialized cognitive functions. The impairment of AMPA receptor-mediated glutamatergic transmission can result in cognitive deficits (Reisel et al, 2002), and the hippocampal AMPA receptor activation is necessary for the process of memory consolidation and retention (Yoshihara and Ichitani, 2004).…”
Section: Introductionmentioning
confidence: 99%